Enhanced nitrogen removal of the simultaneous partial nitrification, anammox and denitrification (SNAD) biofilm reactor for treating mainstream wastewater under low dissolved oxygen (DO) concentration. (July 2019) - Zheng, Zhaoming; Huang, Shan; Bian, Wei; Liang, Dongbo; Wang, Xiujie; Zhang, Kai; Ma, Xiaoran; Li, Jun
Highlights: A SNAD biofilm reactor was well operated under low DO concentration. TIN removal efficiency and TIN removal rate reached 92.7% and 0.30 kg N·m −3 ·d −1 . Enriching bacteria and well mixed biofilm enhanced the reactor performance. Candidatus Anammoxoglobus was the abundant anammox bacteria genus in biofilm. Abstract: The simultaneous partial nitrification, anammox and denitrification (SNAD) process for treating mainstream wastewater was investigated under different intermittent aeration modes. By controlling the aeration time of 20, 60 and 180 min during the intermittent modes, the oxygen concentration remained 3.50, 1.45 and 0.70 mg·L −1 . Correspondingly, the reactor achieved the nitrogen removal rate of 0.17, 0.29 and 0.30 kg N·m −3 ·d −1 . Meanwhile, the average total inorganic nitrogen (TIN) removal efficiency reached 93.4%, 87.5% and 92.7%. The effluent NO3 − -N concentration was very low. High-throughput sequencing analysis indicated that the proportion of nitrite oxidization bacteria (NOB), anammox bacteria and denitrification bacteria was 0.15%, 0.33% and 8.78%. Candidatus Anammoxoglobus was the abundant anammox bacteria genus. Further study on the unclassified sequences revealed the possibility of the high relative abundance of Nitrosomonas-related genus and Candidatus Kuenenia-related genus on the SNAD biofilm.